Gut–brain and brain–gut axis in Parkinson's disease models: Effects of a uridine and fish oil diet. (3rd July 2018) - Perez-Pardo, Paula; Dodiya, Hemraj B.; Broersen, Laus M.; Douna, Hidde; van Wijk, Nick; Lopes da Silva, Sofia; Garssen, Johan; Keshavarzian, Ali; Kraneveld, Aletta D.
Abstract : Recent investigations have focused on the potential role of gastrointestinal (GI) abnormalities in the pathogenesis of Parkinson's disease (PD). The 'dual-hit' hypothesis of PD speculates that a putative pathogen enters the brain via two routes: the olfactory system and the GI system. Here, we investigated (1) whether local exposures of the neurotoxin rotenone in the gut or the brain of mice could induce PD-like neurological and GI phenotypes as well as a characteristic neuropathology in accordance with this 'dual-hit hypothesis' and (2) the effects of a diet containing uridine and fish oil providing docosahexaenoic acid (DHA), in both models. Mice were given rotenone either orally or by an injection in the striatum. Dietary interventions were started 1 week before rotenone exposures. We found that (1) both oral and intrastriatal administration of rotenone induced similar PD-like motor deficits, dopaminergic cell loss, delayed intestinal transit, inflammation, and alpha-synuclein accumulation in the colon; (2) the uridine and DHA containing diet prevented rotenone-induced motor and GI dysfunctions in both models. The models suggest possible bidirectional communication between the gut and the brain for the genesis of PD-like phenotype and pathology. The dietary intervention may provide benefits in the prevention of motor and non-motor symptoms in PD.